Structural Model of Factors Affecting the Use of Organic Fertilizers by Rice Farmers during Rice (Oryza sativa) Cultivation in Dezful County - Zahra Eskanadari; Moslem Saavri; Masoud Yazdanpanah (بوم شناسی کشاورزی)
IntroductionAgriculture is an essential part of every country’s economy and plays a decisive role in income, employment, and food security globally. Agricultural soils are critical for the efficient production of crops and safe food to meet the needs of a growing population. However, improving soil quality is a critical component of sustainable agriculture. Given the socio-economic and political pressure to improve soil fertility and increase agricultural productivity, widespread chemical fertilizer use, beginning in the 1950s and 1960s, led to increased food production at significant environmental cost. Chemical fertilizers and pesticides have improved short-term food production. However, soil degradation, greenhouse gas emission increases, and water pollution risks have emerged through their widespread use. Consequently, excessive use of chemical fertilizers negatively impacts human health throughout the food chain. For example, excessive use of phosphate fertilizers can lead to cadmium pollution, which if ingested can lead to osteoporosis. Excessive use of nitrogen fertilizer leads to the accumulation of nitrites in plants; nitrites combine with amines increasing the risk of cancers of the digestive system, and methemoglobinemia in severe cases. Fertilizer use leads to surface runoff and groundwater pollution contributing to eutrophication and consequently the deterioration of natural ecosystems and reduction of genetic diversity. Rice is one of the main Iranian foods, but the excessive use of chemical inputs in the production of this product has reduced its quality and properties, previous research shows that it is possible to use organic fertilizers in rice cultivation. It can provide nutrients needed by the soil to produce this product. But rice farmers do not have much desire to use it in rice cultivation. In line with this importance, the present study was conducted with the general aim of investigating the factors affecting the use of organic fertilizers by rice farmers during rice cultivation in Dezful county.  Materials and MethodsThe statistical population of this research in 1401 is made up of 4700 rice farmers of Dezful County, and the sample size was estimated based on the table of Karjesi and Morgan, using the cluster sampling method of 360 samples. Data collection was designed in the form of a questionnaire based on the Likert spectrum scale. The form and content validity of the questionnaire was confirmed by experts' opinion and its reliability was confirmed through Cronbach's alpha and composite reliabilityResults and DiscussionThe results of the structural equation modeling research showed that the variables of self-efficacy (ƛ=0.257; P=0.000), action guide (ƛ=0.222; P=0.000), perceived intensity (ƛ=0.121; P=0.035) and perceived sensitivity (ƛ= 0.100; P= 0.046) and perceived benefits (ƛ= 0.319; P= 0.000) have a positive and significant effect on the use of organic fertilizers among rice farmers in Dezful County. This is despite the fact that the perceived obstacles variable did not have a significant effect in this section. In addition, it can be said that the variables of the health belief framework could explain 67% of the variance of the dependent variable of the research (the use of organic fertilizers in rice cultivation). In general, the results of this research can add new knowledge to the existing knowledge and provide new insights for policy makers in this field to promote and develop organic and safe products. ConclusionThis study was conducted with the general aim of determining the factors affecting farmers' willingness to use organic fertilizers in rice cultivation. In this study, the health belief model was used to identify the factors. The results showed that this theory is very efficient in this field because it was able to explain 67% of the variance in farmers' behavior in this field. In general, the results of this study can provide new insights for policymakers in this field in order to produce healthy products.